Maximal isometric and eccentric hamstring strength is influenced by body mass and additional load: Does the critical point at which peak knee flexor force is achieved play a role? - Sinulingga, Andrew Rinaldi; Zemková, Erika (Frontiers in Physiology, 2025)
Isometric (ISO) and eccentric (ECC) hamstring tests are used to assess peak force at various knee angles. However, it is unknown to what extent body weight influences the so-called “critical point” at which individuals achieve their maximal knee flexor force production. This study compared (1) the peak force during maximum voluntary isometric contraction at 60o knee flexion without body weight, with body weight and with added weight, and (2) the eccentric knee flexor strength during Nordic hamstring exercise (NHE) up to 60o of knee flexion with body weight and added weight, as well as up to an angle of 20o with body weight only. The relationship between peak isometric strength in all loading conditions and eccentric strength during NHE performed to different knee angles was also investigated. 22 male athletes (age 21.7 ± 4.3 years, height 181.6 ± 7.5 cm, body mass 75.4 ± 8.5 kg) completed i) maximal efforts on isometric knee flexion at 60° (ISO60), with body weight (ISO60-BW), and with 5 kg medicine ball (ISO60-BW + AW), ii) NHE with lean forward from 90o to 60° with body weight (ECC60-BW) and a 5 kg medicine ball (ECC60-BW + AW), and iii) NHE with lean forward up to 20o with body weight (ECC20). Results showed higher peak force during ISO60-BW + AW compared to ISO60-BW (24.2 N, 6.5%, p = 0.012), and ISO60 (42.1 N, 11.6%, p = 0.000). The added 5 kg (ECC60-BW + AW) produced greater eccentric force compared to body weight (ECC60-BW) (17.9 N, 6.4%; p = 0.03). However, there was no significant difference between NHE with body weight and added weight, irrespective of the subject’s ability to achieve a final position of 20o of knee flexion. Relative eccentric force was higher in participants who achieved 20° than in those who reached their critical point at 45° of knee flexion (p = 0.001, d = 1.89). Peak isometric force in all three conditions significantly correlated with NHE peak force at 45° (r = 0.79–0.90) and 20° of knee flexion (r = 0.71–0.77), explaining 62%–81% and 49%–58% of the variance, respectively. These findings indicate that isometric and eccentric measures of hamstring strength are interdependent. However, eccentric hamstring strength during NHE is more dependent on maximal hamstring strength when this exercise is performed to a critical point of 45° than 20° of knee flexion.